STUDENTS’ MOTIVATION TOWARDS ENGLISH IN STATE POLYTECHNIC OF FAKFAK WEST PAPUA - Titing Magfirah; Riyadh Arridha (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2019)
The purpose of the study was to find out students’ motivation towards English in State Polytechnic of Fakfak, West Papua. The participants of the study were 53 students from Informatics Management Study Program. The instrument used in the data collection was a questionnaire that consists of 20 indicators where 9 indicators refer to instrumental motivation, and 11 indicators are integrative motivation, and 2 open-ended questions were aimed to know another students’ motivation in learning English. Then, the data were analyzed descriptively. The finding indicates that the majority of students at Informatics Management Study Program have integrative motivation in learning English. However, it is also possible that the students have both integrative and instrumental motivations. Based on the students’ responses from open-ended questions, most of the students learn English because it is useful in getting an excellent job in the future, to study or work abroad, to pass an English proficiency test and to be able to read English materials, and also to make friends with English native speakers. Thus, in learning English, motivation is crucial to determine the learners’ achievement. As Dornyei (1998) indicated that it is very possible to successfully reach goals and good achievement with sufficient motivation.